LANGUAGE AND CULTURE IMMERSION: MENINGKATKAN KOMPETENSI BAHASA INGGRIS DAN PEMAHAMAN BUDAYA DI PERBATASAN - Dharma, Yokie; Elisa, Henry; Meo, Ferdinanda Itu (JPPM: Jurnal Pelayanan dan Pemberdayaan Masyarakat, 2024)
Community Service Activities by the English Language Education Lecturer Team of STKIP Persada Khatulistiwa Sintang at PKBM Dorit Tunggal, Sebuduh Village, Kembayan District, Sanggau Regency, aim to improve English language skills based on culture. This program involves 25 participants consisting of students and PKBM tutors through interactive approaches such as presentations, discussions, and practices. The first material discusses the integration of local cultural elements—such as folklore, dances, and traditional songs—in English language learning, in order to introduce Indonesian cultural identity to the world. The second material teaches daily conversations based on relevant local contexts, helping participants practice using English in real life. The results of the activity show that this culture-based approach increases participants' motivation, confidence, and understanding of English while strengthening their appreciation of local culture. Active discussions and independent practice help participants develop language skills with more confidence. This program also promotes local culture to the global level, creating synergy between the academic world and society. Through collaboration between lecturers, students, and the community, this activity not only provides short-term benefits but also builds a foundation for ongoing learning and broader cultural promotion. This approach is expected to become a model for community empowerment in other areas.